2020
DOI: 10.1038/s41467-019-14168-0
|View full text |Cite
|
Sign up to set email alerts
|

Strategy to control magnetic coercivity by elucidating crystallization pathway-dependent microstructural evolution of magnetite mesocrystals

Abstract: Mesocrystals are assemblies of smaller crystallites and have attracted attention because of their nonclassical crystallization pathway and emerging collective functionalities. Understanding the mesocrystal crystallization mechanism in chemical routes is essential for precise control of size and microstructure, which influence the function of mesocrystals. However, microstructure evolution from the nucleus stage through various crystallization pathways remains unclear. We propose a unified model on the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…The polymorphism of ferric oxyhydroxide as an intermediate significantly affects the crystallisation mechanism of Fe 3 O 4 mesocrystals 17 , 18 , 23 25 . We recently identified two Fe 3 O 4 crystallisation pathways starting from either lepidocrocite or goethite and revealed that Fe 3 O 4 mesocrystals grew via OA only in the former case 23 . These pathways are competitively responsible for Fe 3 O 4 growth and can be selectively regulated according to the initial [OH – ]/[Fe 3+ ] ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The polymorphism of ferric oxyhydroxide as an intermediate significantly affects the crystallisation mechanism of Fe 3 O 4 mesocrystals 17 , 18 , 23 25 . We recently identified two Fe 3 O 4 crystallisation pathways starting from either lepidocrocite or goethite and revealed that Fe 3 O 4 mesocrystals grew via OA only in the former case 23 . These pathways are competitively responsible for Fe 3 O 4 growth and can be selectively regulated according to the initial [OH – ]/[Fe 3+ ] ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Surface oxygen vacancies can serve as the activation sites of O 2 molecules, probably reducing the energy barrier of oxygen species regeneration. Meanwhile, the Ce–Ce homogeneous interface and bulk oxygen vacancies reduce the activation and migration barriers of reactive oxygen species . Therefore, CeO 2 –MC tends to exhibit much better catalytic performance.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the Ce−Ce homogeneous interface and bulk oxygen vacancies reduce the activation and migration barriers of reactive oxygen species. 53 Therefore, CeO 2 −MC tends to exhibit much better catalytic performance.…”
Section: Structural Defects and Oxygen Vacanciesmentioning
confidence: 99%
“…The oxolation process is the formation of oxo bridges (−Fe–O–Fe−) accompanied by expelling of molecular water . The primary colloidal particles then aggregate, which allows the heterogeneous nucleation of anhydrous iron oxides, including MNPs. ,,,, This advanced model for magnetite nucleation has been proposed based on data acquired from time-resolved and/or conventional measurements using sophisticated analytical/reactor tools such as liquid-cell transmission electron microscopy (TEM), cryo-TEM, microfluidic reactors, titration reactors, dynamic light scattering, analytical ultracentrifugation, synchrotron-based X-ray diffraction (XRD), small- and wide-angle X-ray scattering (SAXS/WAXS), atomic force microcopy, and field-emission scanning electron microscopy (FESEM). In these experimental studies, direct nucleation of MNPs from ionic solutions has been rarely invoked and measured. , Two main approaches have been proposed to explain the formation of magnetite.…”
Section: Introductionmentioning
confidence: 99%